Comparison of the selection of nasotracheal tube diameter based on the patient’s sex or size of the nasal airway: A prospective observational study - Kim, Hye Jin (PLoS One, 2021)
When selecting the nasotracheal tube diameter for nasotracheal intubation, atraumatic introduction of the tube through the nasal passage and a safe location of the tube’s cuff and tip should be ensured simultaneously. To maintain safety margin for the tube’s cuff and tip from the vocal cords and carina (2 cm and 3 cm, respectively), the maximum allowable proximal-cuff-to-tip distance was calculated as 5 cm less than the measured vocal cords-to-carina distance. The primary aim of this study was to find a single predictive preoperative factor of the nostril size and maximum allowable proximal-cuff-to-tip distance of nasotracheal tubes. The secondary aim was to compare the difference in the safety margin between the maximum allowable proximal-cuff-to-tip distance based on the patient’s airway and the actual proximal-cuff-to-tip distance of the selected tube. We used fiberoptic bronchoscope to measure the distance from the vocal cords to the carina for the calculation of the maximum allowable proximal-cuff-to-tip distance. We analyzed the association of preoperative characteristics such as age, sex, height, and weight with the nostril size and maximum allowable proximal-cuff-to-tip distance. The proportion of patients with appropriate locations of both the cuff and tip was evaluated. Sex and height were significant predictive factors of the nostril size and maximum allowable proximal-cuff-to-tip distance, respectively (p = 0.0001 and p = 0.0048). The difference in the safety margin was significantly decreased when the tube diameter was selected based on the nostril size rather than by sex (p<0.0001). The proportion of patients who had the appropriate cuff/tip location was significantly larger (75.2%) when the tube diameter was selected by sex compared to when it was selected by the nostril size (65%) (p<0.0001). It is more suitable to select the nasotracheal tube diameter based on sex rather than by nostril size to ensure the safe location of the tube’s cuff and tip simultaneously.